Effect of high- and low-resistance inspiratory muscle training on physiological response to exercise in cross-country skiers - Klusiewicz, A.; Starczewski, M.; Sadowska, D.; Ladyga, M. (The Journal of Sports Medicine and Physical Fitness, 2019)
BACKGROUND: The aim of the study was to evaluate the effect of different kinds of respiratory muscle training (RMT) on work capacity and selected spirometric indices in trained male cross-country skiers. METHODS: The study involved 13 competitively trained, elite Polish male cross-country skiers. The subjects were randomly divided into two groups who completed 7 weeks of RMT: one with gradually increasing resistance (power RMT) and the other with constant resistance (endurance RMT). Both groups` training programs consisted of 30 inspiratory maneuvers performed twice a day, 6 days a week. The first week of RMT started with a low resistance (29 cmH2O). In the following weeks, resistance in the power RMT group was gradually increased, while in the endurance RMT group, inspiratory resistance was maintained at a constant level of 53 cm H2O (36±8% PImax). Maximal inspiratory pressure (PImax), peak inspiratory flow rate (PIF), and stress test indices were measured before and after RMT. The stress test was conducted on a ski ergometer, with a gradual increase in intensity in all-out effort. RESULTS: A significant increase in PImax, PIF, and exercise work capacity (test time, work output, and peak power) was noted in both groups. No significant changes were observed in the VO2max or the selected respiratory variables. CONCLUSIONS: During a short training period (up to 7 weeks), the use of gradual and constant inspiratory resistance during RMT improves exercise and spirometric parameters in a similar way. RMT did not have a considerable impact on breathing efficiency in maximal effort.